Design and control of a GYRO stabilized pan-tilt sensor system for mobile applications - Shintemirov, A.; Niyetkaliyev, A. S.; Begalinova, A. M. (Nazarbayev University, 2014)
Pan-tilt platforms are the motion control systems mostly used for controlled positioning of various devices (video cameras, sensors, antennas) in mobile applications such as aerial video surveillance systems, mobile robots for emergency situations, space rovers, defense modules and many others. In this project, a spherical parallel manipulator (SPM) platform is studied for designing a 3DOF system of pure rotation for optimal platform orientations suitable for mobile applications. An optimal trajectory generation and an orientation stabilization control systems will be designed using Model Predictive Control techniques and implemented on the platform prototype.
Keywords: video surveillance systems; mobile robots; space rovers; pan-tilt platforms; mechanical design; design